Grape seed extract (GSE) inhibits angiogenesis via suppressing VEGFR signaling pathway - Wen, Wei (2008)
Blockade of angiogenesis is an important approach for cancer treatment and prevention. VEGF is one of the most critical factors that induce angiogenesis and has thus become an attractive target for anti-angiogenesis treatment. However, most of current anti-VEGF agents often cause some side effects when given chronically. Identification of naturally occurring VEGF inhibitors derived from diet would be one alternative approach with an advantage of known safety. Grape seed extract (GSE), a widely used dietary supplement, is known to have anti-tumor activity. In this study, we have explored the activity of GSE on VEGF receptor and angiogenesis. We found that GSE could directly inhibit kinase activity of purified VEGFR2, a novel activity of GSE that has not been characterized. GSE could also inhibit VEGFR/MAPK mediated signaling pathway in endothelial cells. As a result, GSE could inhibit VEGF induced endothelial cell proliferation and migration as well as sprouts formation from aorta ring. In vivo assay further showed that GSE could inhibit tumor growth and tumor angiogenesis of MDA-MB-231 breast cancer cells in mice. Consistent with the in vitro data, GSE treatment of tumor bearing mice led to concomitant reduction of blood vessel density and phosphorylation of MAP kinase. Depletion of polyphenol with polyvinylpyrrolidone (PVPP) abolished the anti-angiogenesis activity of GSE, suggesting a water soluble fraction of polyphenol in GSE is responsible for the anti-angiogenesis activity. Taken together, this study indicates that GSE is a well tolerated and inexpensive natural VEGF inhibitor and could potentially be useful in cancer prevention or treatment.